Nanotexturing TiO2 over carbon nanotubes for high-energy and high-power density pseudocapacitors in organic electrolytes - Poirot, N.; Rajalingam, V.; Murgu, R. N.; Omnée, R.; Raymundo-Piñero, E. (Frontiers in Materials, 2022)
Titanium oxides have been considered potential electrode materials for pseudocapacitors because of their exceptional properties, such as high thermal and chemical stabilities, ready availability and low cost. However, they are not ideal for practical applications due to their poor ionic and electrical conductivity. The electrochemical performance of TiO2 can be greatly improved if the material is nanotextured by reducing the particle size in optimizing the synthesis pathway. Actually, for metallic oxides, the electrochemical performance significantly depends on the particle size/morphology. At relatively low current densities the higher capacity values are exhibited by noncrystalline TiO2 having 2 nm particle size, with values reaching 704 C.g-1. However, only thin electrodes are able to operate at a high charge density, limiting the energy density of the final device. Here, we propose a solution to circumvent such a drawback by further nanotexturing TiO2 over multiwalled carbon nanotubes (CNTs). For that purpose, CNTs were introduced during oxide preparation. The synthesis protocol has been optimized for obtaining a uniform coverage of small TiO2 particles on the surface of the CNTs. At low current densities, high mass loading TiO2/CNT composites electrodes are able to deliver capacitances as high as 480 F.g-1 and the presence of CNTs allows keeping 70 % of the capacitance at high current densities while only 27 % is retained when using a regular conductivity agent as carbon black. The results demonstrate that uniform nanotexturation of TiO2 over CNTs allows good rate capabilities to be obtained for thick electrodes having sufficient active material loading to achieve high specific energy and power densities.